Efficiency Analysis of Provincial Government Expenditures on Education in Indonesia (Before and After Fiscal Decentralization) - Sylviana, Widya; Suyanto, Suyanto; Bin Abdul Karim, Zulkefly; Ã¼nlÃ¼kaplan, Ilter (EcceS: Economics, Social, and Development Studies, 2024)
Fiscal decentralization is closely tied to a country's economic development, with one of its main objectives being the enhancement of public service efficiency, particularly government spending. Government expenditures reflect policy decisions, including providing essential services such as education through HDI. However, many studies dispute the notion that decentralization automatically improves resource allocation efficiency. This research aims to: 1) assess the efficiency of government spending on education in regencies and cities before and after fiscal decentralization, and 2) identify factors influencing this efficiency. The study uses Data Envelopment Analysis (DEA) to evaluate efficiency levels and Tobit regression to analyze the factors affecting efficiency. DEA results show that regencies and cities in Papua have the lowest efficiency (63%), while those in Sumatera have the highest (92%). The Tobit regression model indicates that, for the pre-decentralization period, only the student-teacher ratio is significant, while after decentralization, population size, student-teacher ratio, and region dummy become significant. The findings suggest that improving efficiency in education spending, both before and after decentralization, is critical. Future research should expand the study period, include other sectors like health, and consider the role of the private sector in education. This study contributes to understanding fiscal decentralization's impact on education efficiency and its broader implications for regional and national development.